IoT-Based Portable and Tracking Device for Children Safety - Tong, Tiam Yong; Zainal, Nurfarina (Evolution in Electrical and Electronic Engineering, 2023)
Recently, there has been a drastic increase in crime rates, especially the missing child cases. The children while growing up may be premature in the way they act and face many safety issues such as being abducted in crowded areas and social bullying. Besides, the harassment of strangers has deep effects on a child’s physical health. At the moment, most of the portable tracking devices available today are only focused on providing the location and activity of the children. However, lacks the health and alert notification system. Therefore, an IoT-based portable and tracking device was developed to help parents to monitor their child’s physical health such as heart rate, beat per minute (BPM) and blood oxygen saturation (SpO2), as well as to track their location in real-time with the alert notification. The alert notification can be sent automatically through email and push notification from the Blynk IoT application in the smartphone when the child’s situation whether in abnormal condition. The system detected abnormal conditions for heart rate in the range of <60 BPM or 99 BPM. While values of blood oxygen saturation (SpO2) is < 95 %. The system consists of an ESP32 Microcontroller, heart rate pulse sensor and oximeter module (GY-MAX30100), a global positioning system (GPS-NEO6M), lithium battery 3.7V, Blynk as a cloud server and the internet. With the usage of Internet of things (IoT) technologies, the number of missing child cases can be minimized. The system was developed successfully with a prototype of a watch strap and Blynk mobile application which allows the parents to monitor their children in real-time. Recently, there has been a drastic increase in crime rates, especially the missing child cases. The children while growing up may be premature in the way they act and face many safety issues such as being abducted in crowded areas and social bullying. Besides, the harassment of strangers has deep effects on a child’s physical health. At the moment, most of the portable tracking devices available today are only focused on providing the location and activity of the children. However, lacks the health and alert notification system. Therefore, an IoT-based portable and tracking device was developed to help parents to monitor their child’s physical health such as heart rate, beat per minute (BPM) and blood oxygen saturation (SpO2), as well as to track their location in real-time with the alert notification. The alert notification can be sent automatically through email and push notification from the Blynk IoT application in the smartphone when the child’s situation whether in abnormal condition. The system detected abnormal conditions for heart rate in the range of <60 BPM or 99 BPM. While values of blood oxygen saturation (SpO2) is < 95 %. The system consists of an ESP32 Microcontroller, heart rate pulse sensor and oximeter module (GY-MAX30100), a global positioning system (GPS-NEO6M), lithium battery 3.7V, Blynk as a cloud server and the internet. With the usage of Internet of things (IoT) technologies, the number of missing child cases can be minimized. The system was developed successfully with a prototype of a watch strap and Blynk mobile application which allows the parents to monitor their children in real-time.